One-Pot Synthesis of Spirotetrahydrooxino[3,4-c]pyridines and Spirotetrahydrofuro[3,2-b]pyridin-2-ones via Lactonization from Activated Pyridyldihydroozaxoles and Bis(trimethylsilyl)ketene Acetals - Gómez-García, Omar; Gómez, Elizabeth; Toscano, Rubén A.; Salgado-Zamora, Héctor; Álvarez-Toledano, Cecilio (Synthesis, 2016)
5-Methyl-2-(pyridin-3-yl)-4,5-dihydrooxazole and 5-methyl-2-(pyridin-4-yl)-4,5-dihydrooxazole activated by triflic anhydride underwent lactonization with bis(trimethylsilyl)ketene acetals to provide tetrahydrooxino[3,4-c]pyridines and tetrahydrofuro[3,2-b]pyridin-2-ones. Formation of the product was controlled by the position of the pyridyl substituent at C-3 and C-4 of the pyridyldihydrooxazole. On the other hand, 1-(trifluoromethylsulfonamido)propan-2-yl picolinate was obtained under the same conditions from 5-methyl-2-(pyridin-2-yl)-4,5-dihydrooxazole.
Keywords: lactonization; pyridyldihydrooxazoles; ketene acetals; spirotetrahydrofuro[3,2-b]pyridin-2-ones; spirotetrahydrooxino[3,4,-c]pyridines